The evolution of alkaliphilic biofilm communities in response to extreme alkaline pH values. Issue 4 (16th August 2022) - Charles, Christopher J.; Rout, Simon P.; Jackson, Brian R.; Boxall, Sally A.; Akbar, Sirwan; Humphreys, Paul N.
Abstract: Extremes of pH present a challenge to microbial life and our understanding of survival strategies for microbial consortia, particularly at high pH, remains limited. The utilization of extracellular polymeric substances within complex biofilms allows micro‐organisms to obtain a greater level of control over their immediate environment. This manipulation of the immediate environment may confer a survival advantage in adverse conditions to biofilms. Within the present study alkaliphilic biofilms were created at pH 11.0, 12.0, or 13.0 from an existing alkaliphilic community. In each pH system, the biofilm matrix provided pH buffering, with the internal pH being 1.0–1.5 pH units lower than the aqueous environment. Increasing pH resulted in a reduced removal of substrate and standing biomass associated with the biofilm. At the highest pH investigated (pH 13.0), the biofilms matrix contained a greater degree of eDNA and the microbial community was dominated by Dietzia sp. and Anaerobranca sp. Abstract : Flocculants were used to seed biofilms in alkaline conditions (pH 11.0–13.0). Biofilms had pH and redox values lower than that of the external environment. Extracellular polymeric materials comprising the biofilm may play a role in these changes.